Functional Characterization of a Variant Prekallikrein (PK Zürich) - Wuillemin, W A; Furlan, M; von Felten, A; Lämmle, B (Thrombosis and Haemostasis, 1993)
The plasma of a 68-year-old man with cross reacting material (CRM)-positive prekallikrein (PK) deficiency was studied. PK clotting activity was <0.01 U/ml, and PK antigen was 0.1 U/ml. No circulating anticoagulant against PK was detectable. The abnormal PK molecule, denoted as prekallikrein Zürich, was partially characterized by immunological and functional studies on the propositus’ plasma. Immunobiotting analysis showed the abnormal PK being a single chain molecule of the same Mr (80 kDa) as normal PK. Dextran sulfate activation of the propositus’ plasma did not lead to proteolytic cleavage of the variant PK molecule, in contrast to dextran sulfate activation of a mixture of 1 volume normal plasma and 9 volumes CRM-negative PK deficient plasma. Agarose gel electrophoresis followed by immunoblotting demonstrated that PK Zürich was complexed with high molecular weight kininogen similarly to PK in normal plasma. Incubation of the propositus’ plasma with purified β-FXIIa resulted in impaired cleavage of PK Zürich when compared with PK hydrolysis in a mixture of 10% normal plasma and 90% CRM-negative PK deficient plasma. Moreover, proteolytically cleaved PK Zürich showed no enzymatic activity against factor XII and high molecular weight kininogen.These studies show that the functional defect of prekallikrein Zürich is due to an impaired cleavage by activated factor XII and probably the lack of enzymatic activity of the cleaved variant molecule.